Rosuvastatin Enhances the Catabolism of LDL apoB‐100 in Subjects with Combined Hyperlipidemia in a Dose Dependent Manner. Issue 5 (26th March 2015) - Le, Ngoc‐Anh; Diffenderfer, Margaret R.; Thongtang, Nuntakorn; Ooi, Esther M. M.; Barrett, P. Hugh R.; Horvath, Katalin V.; Dolnikowski, Gregory G.; Asztalos, Bela F.; Schaefer, Ernst J.; Brown, W. Virgil
Abstract: Dose‐associated effects of rosuvastatin on the metabolism of apolipoprotein (apo) B‐100 in triacylglycerol rich lipoprotein (TRL, d < 1.019 g/ml) and low density lipoprotein (LDL) and of apoA‐I in high density lipoprotein (HDL) were assessed in subjects with combined hyperlipidemia. Our primary hypothesis was that maximal dose rosuvastatin would decrease the apoB‐100 production rate (PR), as well as increase apoB‐100 fractional catabolic rate (FCR). Eight subjects received placebo, rosuvastatin 5 mg/day, and rosuvastatin 40 mg/day for 8 weeks each in sequential order. The kinetics of apoB‐100 in TRL and LDL and apoA‐I in HDL were determined at the end of each phase using stable isotope methodology, gas chromatography‐mass spectrometry, and multicompartmental modeling. Rosuvastatin at 5 and 40 mg/day decreased LDL cholesterol by 44 and 54 % (both P < 0.0001), triacylglycerol by 14 % (ns) and 35 % ( P < 0.01), apoB by 30 and 36 % (both P < 0.0001), respectively, and had no significant effects on HDL cholesterol or apoA‐I levels. Significant decreases in plasma markers of cholesterol synthesis and increases in cholesterol absorption markers were observed. Rosuvastatin 5 and 40 mg/day increased TRL apoB‐100 FCR by 36 and 46 % (both ns) and LDL apoB‐100 by 63 and 102 % (both P < 0.05), respectively. HDL apoA‐I PR increased with low dose rosuvastatin (12 %, P < 0.05) but not with maximal dose rosuvastatin. Neither rosuvastatin dose altered apoB‐100 PR or HDL apoA‐I FCR. Our data indicate that maximal dose rosuvastatin treatment in subjects with combined hyperlipidemia resulted in significant increases in the catabolism of LDL apoB‐100, with no significant effects on apoB‐100 production or HDL apoA‐I kinetics.